2019
DOI: 10.1002/ente.201900271
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of B and Al Dopants in Mesoporous MFI Nanocrystals for Highly Selective Alcoholysis of Furfuryl Alcohol into Ethyl Levulinate

Abstract: In this article, the synergetic effect between the B‐ and Al‐based acidic sites in B–Al co‐doped mesoporous MFI nanocrystals (denoted as m‐B‐Al‐S1) is rationally applied to modify the alcoholysis process of furfuryl alcohol. The porosity and dopant concentration of the m‐B‐Al‐S1 materials are optimized via a modified Kirkendall growth method to boost the ultra‐high selectivity to ethyl levulinate reactions (94%). The m‐B‐Al‐S1 catalyst also shows good stability for further reuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The yield of EL increased with the calcination temperature for either the ZrO 2 ‐T‐1.5 catalysts or the ZrO 2 ‐M‐1.5 catalysts, and the yield of EL reached 96.4% over 500‐M‐1.5 catalyst, whereas it reached 94.5% over 500‐T‐1.5 catalyst. The catalytic activity of the 500‐M‐1.5 catalyst developed in this study was also compared with other typical catalysts developed/used in other studies for the conversion of FA to EL (Table S3, Supporting Information) . The results clearly indicated that the catalyst developed herein showed superior or comparable activities to the reported catalysts.…”
Section: Resultsmentioning
confidence: 54%
“…The yield of EL increased with the calcination temperature for either the ZrO 2 ‐T‐1.5 catalysts or the ZrO 2 ‐M‐1.5 catalysts, and the yield of EL reached 96.4% over 500‐M‐1.5 catalyst, whereas it reached 94.5% over 500‐T‐1.5 catalyst. The catalytic activity of the 500‐M‐1.5 catalyst developed in this study was also compared with other typical catalysts developed/used in other studies for the conversion of FA to EL (Table S3, Supporting Information) . The results clearly indicated that the catalyst developed herein showed superior or comparable activities to the reported catalysts.…”
Section: Resultsmentioning
confidence: 54%
“…Biofuels derived from biomass offer sustainable alternatives to fossil fuels for transportation and chemical production. They are carbon-neutral, as the emitted carbon dioxide is absorbed by plants . Biomass is widely available, renewable, and recyclable, making it an attractive energy source. Ethyl levulinate (EL), derived from biomass, has desirable properties and finds applications in biofuels, fuel additives, pharmaceutical intermediates, and green solvents. , However, traditional catalysts for EL production can cause pollution, equipment corrosion, and separation issues. , Therefore, the selection of catalysts for EL synthesis should consider environmental and economic factors, aiming for ease of separation, eco-friendliness, stability, high activity, and cost-effectiveness. , In industry, furfuryl alcohol (FA) obtained directly from pentose hydrolysis is commonly used as a raw material for producing EL. This approach not only saves resources but also simplifies the purification process for the final products. , …”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 However, traditional catalysts for EL production can cause pollution, equipment corrosion, and separation issues. 10 , 11 Therefore, the selection of catalysts for EL synthesis should consider environmental and economic factors, aiming for ease of separation, eco-friendliness, stability, high activity, and cost-effectiveness. 12 , 13 In industry, furfuryl alcohol (FA) obtained directly from pentose hydrolysis is commonly used as a raw material for producing EL.…”
Section: Introductionmentioning
confidence: 99%
“…Various catalysts were studied for conversion of FA to EL, and several reviews were reported on this topic. , Solid acid catalysts have attracted more attention than homogeneous acids and ionic liquids, because of their easy recovery and separation. ,, Among the solid catalysts, metal salts, solid catalysts with sulfonic acid groups, and ion-exchange resins showed promising performance, but they are faced with such problems as environmental pollution, leaching of active components, or difficulty in regeneration by their limited thermal stability. In contrast, zeolites have the advantages of low cost and easy regeneration by coke burn-off, showing broad prospects for commercial applications. , …”
Section: Introductionmentioning
confidence: 99%